UNSUR–UNSUR PENDIDIKAN KARAKTER DALAM PAI DAN IMPLIKASINYA TERHADAP SIKAP DAN PERILAKU AGAMA SISWA - Siti Solehah (CV Putra Publisher, 2022)
Character are psychological, moral, or character traits that distinguish one person from another. Here, character can also be understood as a character or character. Thus, a person with character is a person who has character, has a personality, or has character. Elements of character Attitude, emotion, belief, habit and will, self-conception. The actions, behavior, and attitudes of children today are not something that suddenly appears or is formed or even